Determinantes da alteração do preço de exportação do milho no período 2000 a 2012 - Furlanetto, Katiane Fabbris (Universidade do Vale do Rio dos Sinos, 2014)
The objective of this study is to indicate the most important determinants in the worldwide exported maize average price in order to provide information to economic agents. Treats the world maize market current situation, starting at 2000 when there was a boom in commodity prices. This way, the econometric model proposed for this study is structured in the statistical model based on panel data on an annual basis between the period 2000 up to 2012. For the analysis better understanding, a review of theoretical and empirical concepts was previously presented in the early chapters, which deals the main factors in defining the exported maize average price. After, the developed exercise was analyzed performing the F test for significance in all the country dummies, in order to prove that this is really a panel data model. Was also defined by the Hausman test that is indicated the fixed effect estimator to this model. Thus, four models were made, and the D model, instrumenting the variable maize export (in kg) with the variable maize export (in kg) lagged 1 period, and it presented most consistent and conclusive results regarding the theoretical basis of the initial chapters. Among the main results, it is evident that the main determinant of the maize export price variation is the real effective exchange rate variable. Also revealed that the variables country maize exports (in kg) to the world; pork meat exports of the main maize export destinations; and urban population of the main maize export destinations are significant.
Keywords: Commodities; Mercado de milho; Modelo de dados em painel; Maize market; Panel data model; ACCNPQ::Ciências Sociais Aplicadas::Economia